1984
DOI: 10.1007/bf00395476
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of glyoxysomes in maturing and germinated cotton seeds?a morphometric analysis

Abstract: Morphometric procedures were used with light and electron microscopy to examine glyoxysome number, volume, shape and distribution as well as mesophyll cell volume, in cotyledons of mature (50 d postanthesis), imbibed (5h) and germinated (24 and 37 h) cotton (Gossypium hirsutum L.) seeds. Additionally, activities of five glyoxysomal marker enzymes in cotyledon extracts were assayed at each of the above ages. Cell volume was determined from photomicrographs of Epon-embedded sections by the point-counting procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…We previously found using morphometric procedures that peroxisomes of cotton cotyledons persist through seed desiccation and increase dramatically in volume (but not number) during postgerminative growth (17). No evidence was found for autophagy or turnover of entire organelles during the entire period studied (17).…”
Section: Kdomentioning
confidence: 87%
See 2 more Smart Citations
“…We previously found using morphometric procedures that peroxisomes of cotton cotyledons persist through seed desiccation and increase dramatically in volume (but not number) during postgerminative growth (17). No evidence was found for autophagy or turnover of entire organelles during the entire period studied (17).…”
Section: Kdomentioning
confidence: 87%
“…Plant Material. Cotton plants, Gossypium hirsutum L. (AD), cv Deltapine 62 (Delta and Pine Land Co., Lubbock, TX) were grown under the conditions described previously (17), and flowers were tagged at anthesis to determine the age ofthe developing embryos. For studies with germinated seeds, acid-delinted seeds were surface sterilized in 1% (v/v) NaOCl for 10 min, rinsed thoroughly, soaked in distilled H20 for 6 h at 30C with aeration, then scrolled in moistened filter paper.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In plant cells, there are numerous examples of terminal peroxisome elongation at different stages of growth and development. Specifically, peroxisomes in cotyledon cells of germinated oilseed seedlings, greening leaves and developing root nodules all undergo dramatic increases in spherical or cylindrical volume, but do not increase in number (Gruber et al, 1973;Wanner and Theimer, 1978;Kunce et al, 1984;Newcomb et al, 1985). Exposure of Arabidopsis suspension cells to ultraviolet (UV) irradiation induces extensive peroxisomal elongation without subsequent multiplication (proliferation) (our unpublished observations).…”
Section: Peroxisome Elongationmentioning
confidence: 91%
“…Collings et al observed horseshoe-and dumbbell-shaped peroxisomes at the cell plate within the phragmoplast of dividing onion-root meristem cells (Collings et al, 2003). Kunce et al documented elongation of glyoxysomes in cotyledons of growing cottonseed seedlings (Kunce et al, 1984). Significantly, no efforts were made in any of these studies to identify molecular elements or machinery related to these proliferative events.…”
Section: Introductionmentioning
confidence: 99%